Genome-wide analysis of long non-coding RNAs and mRNAs in lung adenocarcinoma with pulmonary thromboembolism - Ahmat, Maryamgvl; Alim, Gvzalnur; Zhu, Zhu; Chen, Chao; Cao, Guolei; Luo, Qin (Frontiers in Genetics, 2026)
IntroductionPulmonary thromboembolism (PTE) is a serious complication in patients with lung adenocarcinoma (LUAD), yet its molecular mechanisms remain poorly understood. This study aimed to investigate the expression profiles of long non-coding RNAs (lncRNAs) and mRNAs in LUAD patients complicated by PTE.MethodsPeripheral blood samples were collected from LUAD patients with PTE and from three control groups (LUAD-only, PTE-only, and healthy controls). RNA sequencing was performed to identify differentially expressed lncRNAs and mRNAs among groups.ResultsRNA sequencing revealed significant dysregulation of transcripts. Compared with LUAD-only patients, 725 lncRNAs and 2,052 mRNAs were differentially expressed in the LUAD + PTE group. Compared with PTE-only patients, 932 lncRNAs and 2,206 mRNAs were differentially expressed, while comparison with healthy controls identified 1,190 lncRNAs and 3,001 mRNAs. Key dysregulated transcripts included MERGE.31027.6, ENST00000318988, MERGE.30976.2, and ENST00000397519. Enrichment analyses highlighted immune response–related pathways, cytokine signaling, and the NF-κB signaling pathway.ConclusionThese findings suggest that aberrant lncRNA and mRNA expression may contribute to the pathogenesis of LUAD complicated by PTE and may serve as potential biomarkers and therapeutic targets for prognosis and treatment.